2021
DOI: 10.3892/ol.2021.12777
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of microRNA‑223‑3p on breast cancer cell processes via the Hippo/Yap signaling pathway

Abstract: According to the 2018 global cancer statistics, the incidence and mortality rates of breast cancer are increasing gradually, which seriously threatens the health of women. MicroRNA-223-3p (miR-223-3p) can promote the proliferation and invasion of breast cancer cells. Hippo/Yes-related protein (Yap) signaling pathway activation has been found in a variety of tumors. The present study aimed to investigate the potential mechanism of miR-223-3p in breast cancer. The Cell Counting Kit-8 assay was used to detect cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…The upregulation of the microRNAs, miR-223 and miR-28-5p, in the exposed groups was common to both studies [ 35 , 36 ]. miR-223 has been described as a key regulator of innate immune response in respiratory diseases, a protective factor against atherosclerosis and a potential biomarker for breast cancer [ 37–39 ]. Moreover, miR-28-5p has been demonstrated as a potential biomarker for various diseases such as unstable angina, colon cancer, gastrointestinal cancer and prostate cancer [ 40–43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of the microRNAs, miR-223 and miR-28-5p, in the exposed groups was common to both studies [ 35 , 36 ]. miR-223 has been described as a key regulator of innate immune response in respiratory diseases, a protective factor against atherosclerosis and a potential biomarker for breast cancer [ 37–39 ]. Moreover, miR-28-5p has been demonstrated as a potential biomarker for various diseases such as unstable angina, colon cancer, gastrointestinal cancer and prostate cancer [ 40–43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, miR-223-3p enhances the proliferative and migrative abilities of renal clear cell carcinoma cells via down-regulating the expression of solute carrier family 4 member 4 [ 18 ]. MiR-223-3p promotes the malignant biological behaviors of breast cancer cells through Hippo/Yap signal pathway [ 34 ]. In this work, it was revealed that miR-223-3p was highly expressed in OC tissues, which is consistent with previous findings [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of receptor of collagen I, Discoidin Domain Receptor Tyrosine Kinase 2 (DDR2), also confers a susceptibility to ferroptosis via the Hippo pathway (Lin C. C. et al, 2021). In the field of RNAs, miR-223-3p (Du et al, 2021) and long non-coding LINC00649 (Wang H. et al, 2021c) were identified as regulators. Jiang L. et al (2021) revealed that YAP upregulation induces proliferation, migration and EMT progression of colorectal cancer cells through the Glut3/AMPK signaling pathway.…”
Section: Hippo/yap and Rtksmentioning
confidence: 99%